2020
DOI: 10.18421/tem93-50
|View full text |Cite
|
Sign up to set email alerts
|

How Technology Acceptance Model TAM)Factors of Electronic Learning Influence Education Service Quality through Students' Satisfaction

Abstract: The objectives of the study is figuring out of the results of adoption of electronic learning systems (BeSmart) using Technology Acceptance Model (TAM) factors and servqual models to measure the education services. The data was obtained using SEM with AMOS 2.4. From the findings of the study, note that EoU and U of electronic learning systems hava a positive and significant effect on ESQ through student satisfaction. These findings contribute to university management to understand that service quality needs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Song et al [30] introduced users' intentions to use to an electronic file bag application, which confirmed that cognitive constructs in TAM play a mediating role and predict usage intention. The modified TAM has been used for investigating e-learning applications [31]. Moreover, some academics claim that the intrinsic factors impact users' behavior, and have demonstrated the important effects on usage acceptance [1,25,32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Song et al [30] introduced users' intentions to use to an electronic file bag application, which confirmed that cognitive constructs in TAM play a mediating role and predict usage intention. The modified TAM has been used for investigating e-learning applications [31]. Moreover, some academics claim that the intrinsic factors impact users' behavior, and have demonstrated the important effects on usage acceptance [1,25,32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, other research states that electronic learning systems have a positive and significant effect on ESQ through student satisfaction. These findings contribute to university management's understanding of the need for service quality (Sholikah & Sutirman, 2020).…”
Section: Structural Model Resultsmentioning
confidence: 66%
“…The use of Google Sheets application to do accounting assignments for adjusting journal material could not fully increase the productivity of class XII IPS students at Ambulu State High School in learning. A technology system can be said to be beneficial if the system can help users to maximize their performance (Sholikah & Sutirman, 2020).…”
Section: Discussionmentioning
confidence: 99%